2017
DOI: 10.1111/1759-7714.12481
|View full text |Cite
|
Sign up to set email alerts
|

Influence of trainee involvement on procedural characteristics for linear endobronchial ultrasound

Abstract: BackgroundLinear endobronchial ultrasound (EBUS) is a safe and effective method for the diagnostic sampling of mediastinal lymph nodes. However, there is a learning curve associated with the procedure and operator experience influences diagnostic yield. We sought to determine if trainee involvement during EBUS influences procedural characteristics, complication rate, and diagnostic yield.MethodsWe performed a retrospective analysis of 220 subjects who underwent an EBUS procedure at our center from December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…We measured actual clinical outcomes such as diagnostic yield and complication rates while other studies quantified the procedural skills of the trainees. While a dichotomous clinical outcome of diagnostic yield may not provide information on individual trainee's anatomical knowledge and biopsy techniques, it was considered an objective and significant clinical endpoint as opposed to a surrogate endpoint and the definitive measurement of the effectiveness of medical education (9,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We measured actual clinical outcomes such as diagnostic yield and complication rates while other studies quantified the procedural skills of the trainees. While a dichotomous clinical outcome of diagnostic yield may not provide information on individual trainee's anatomical knowledge and biopsy techniques, it was considered an objective and significant clinical endpoint as opposed to a surrogate endpoint and the definitive measurement of the effectiveness of medical education (9,17).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst EBUS-TBNA has been associated with high diagnostic yield and low complication rates, the performance outcome may differ between experts and trainees who perform it under supervision. In a single-center retrospective analysis of 220 subjects undergoing EBUS-TBNA, it was found that procedure time was longer (16 vs. 13.7 min), amount of lidocaine use was higher (322.3 vs. 304.2 mg) and the diagnostic yield was lower (52.6% vs. 68.3%) when comparing trainees to staff physicians performing EBUS-TBNA (9). In another study of 607 procedures, it was reported that there was a higher complication rate in the trainee group (4.7% vs. 1.1%, P=0.076) (10).…”
Section: Introductionmentioning
confidence: 99%
“…An interesting study finding was that trainee involvement was associated with post procedure ED visits after endoscopy. A number of studies have not shown trainee involvement in procedural specialties to be associated with acute care visits or increased adverse events [10,18,19] , but others have found the opposite [20,21] , thus this remains an unanswered question. Possible explanations for our findings might include that fellow participation could have increased procedure time which may result in increased administration of sedation, use of air insufflation, and potentially suboptimal technique which could increase post endoscopy abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
“…This educational model has several shortcomings: It demands a high level of supervision from experienced practitioners; the curriculum is not standardized as it is based on the available patient cases at the institution; and it often uses non-standardized assessment tools for evaluating novices' procedural competence [11]. Furthermore, there is a risk of undue complications as patients are exposed to trainee learning curves [12][13][14].…”
Section: Introductionmentioning
confidence: 99%